2009
DOI: 10.1186/1742-4690-6-47
|View full text |Cite
|
Sign up to set email alerts
|

In vitro nuclear interactome of the HIV-1 Tat protein

Abstract: Background: One facet of the complexity underlying the biology of HIV-1 resides not only in its limited number of viral proteins, but in the extensive repertoire of cellular proteins they interact with and their higher-order assembly. HIV-1 encodes the regulatory protein Tat (86-101aa), which is essential for HIV-1 replication and primarily orchestrates HIV-1 provirus transcriptional regulation. Previous studies have demonstrated that Tat function is highly dependent on specific interactions with a range of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 261 publications
5
87
2
1
Order By: Relevance
“…However, mRNAs of the HIV-1 receptor CD4 and coreceptor CXCR4 genes were upregulated in these cells. Transcripts of factors involved in RNA splicing (PRPF4B, SFRS16, and SFRS17A) were upregulated in latently infected cells, whereas factors mediating nuclear import of Rev (IPO5/RANBP5 [38] and IPO7 [39]) and Tat (NUP93 and NUP153 [40]) were downmodulated in these cells.…”
Section: Latently Infected Cd4mentioning
confidence: 97%
“…However, mRNAs of the HIV-1 receptor CD4 and coreceptor CXCR4 genes were upregulated in these cells. Transcripts of factors involved in RNA splicing (PRPF4B, SFRS16, and SFRS17A) were upregulated in latently infected cells, whereas factors mediating nuclear import of Rev (IPO5/RANBP5 [38] and IPO7 [39]) and Tat (NUP93 and NUP153 [40]) were downmodulated in these cells.…”
Section: Latently Infected Cd4mentioning
confidence: 97%
“…Tat has been shown to regulate the capping of HIV-1 mRNA [269], to interact with Dicer and suppress the production of small interfering RNA [270], and to act as a nucleic acid chaperone [271]. Recently, 183 proteins within the nucleus of Jurkat T cells were found to be cellular targets of Tat [272]. The identified nuclear targets covered a range of biological processes: transcription, RNA processing, translation, nuclear organization, cell cycle, DNA replication, and signaling, with transcription being the most highly represented process (39%).…”
Section: Tatmentioning
confidence: 99%
“…For example, orosomucoid inhibits the infection of human monocyte-derived macrophages by R5 HIV-1 (Atemezem et al 2001; Rabehi et al 1995). Gautier et al have shown that ruvB-like2 is one of the 183 Jurkat T cell nuclear extract proteins that interact with Tat (Gautier et al 2009). In a similar study, Impens et al incubated HIV-1 protease with Jurkat T cell lysates and analyzed the resulting peptides with MS (Impens et al 2012).…”
Section: Resultsmentioning
confidence: 99%